EXERCISE PROGRAM FOR CHILDREN AND ADOLESCENTS WITH DOWN SYNDROME: LITERATURE REVIEW (Fiep Bulletin - online, 2015)
Down syndrome (DS) is a genetic condition that results in particular physical and intellectual characteristics, causing a delay in development. The aim of this study was to determine, by a systematic review of the literature, the exercise protocols employed in children and adolescents with DS. In the research, there were previously established criteria and it was possible to identify thirty studies, but only nine were part of the scope of this review. From this nine studies, three of them regarded aerobic exercise protocols, two were about resistance exercise, two experimented a protocol combination, and there was one vibratory exercise approach. We conclude that all studies showed benefits for this population, however, there is no consensus about the best activity to indicate. We suggest that future studies should propose different exercise protocols for analysis of each variable assessed to establish best parameters for practicing physical activity in this population.
Keywords: Down syndrome; exercise; health promotion